Cotton-elastane ring core spun yarn: A review - Tayari Akankwasa, Nicholus; Siddiqui, Qasim; Kamalha, Edwin; Ndlovu, Llyod (Research & Reviews on Polymer, 2013)
The quest for highly stretchable fabrics with good and lasting handle properties such as absorbance, feel, and comfort has inspired researchers to constantly involve in blending of natural and artificial fibres. One of the commonly used methods of blending is core yarn spinning. Core spun yarn structure consists of two components; the sheath and the core. Normally, a continuous multifilament yarn is used as a core while cotton staple fibres are used to cover the filament. Cotton staple fibres have been a favourite choice for the sheath of core spun yarns because of their aesthetic properties. Cotton is known for its commendable absorbance properties, comfort feel among other unique properties that can hardly be found in most man-made fibres. On the other hand, most filaments used like Lycra, polyester, and spandex, among others possess stretching/extensible properties and they are also responsible for the tensile properties of the resulting yarn. This reviewfocused on structural properties, end use, and the important spinning parameters of Cotton/Lycra, Cotton/spandex, Cotton/Polyester elastic core spun yarns.
Keywords: Core spun yarn; Ring spinning parameters; T-400/Cotton; Cotton/ Polyester; Cotton /Spandex